2008
DOI: 10.1590/s1517-86922008000100013
|View full text |Cite
|
Sign up to set email alerts
|

A suplementação de creatina prejudica a função renal?

Abstract: Enquanto o consumo de creatina por atletas e praticantes de atividade física tem crescido vertiginosamente, os efeitos adversos desse suplemento continuam sendo alvos de calorosos debates científicos, sobretudo no que se refere à função renal. O objetivo dessa revisão é descrever as falhas metodológicas e lacunas na literatura, que contribuem para a divergência do tema. Relatos de caso sugerem que a creatina é um potencial agente nefrotóxico. Em contrapartida, estudos longitudinais, embora possuam diversas lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
(38 reference statements)
0
4
0
17
Order By: Relevance
“…In the end, Cr monohydrate has been the most studied supplement applied on sports performance enhancement and several health conditions. 4,5,58 …”
Section: Other Considerationsmentioning
confidence: 99%
“…In the end, Cr monohydrate has been the most studied supplement applied on sports performance enhancement and several health conditions. 4,5,58 …”
Section: Other Considerationsmentioning
confidence: 99%
“…However, due to its intense use as a nutritional supplement, it is necessary to conduct a careful evaluation on the possible toxicity to metabolism and liver morphology, as well as to renal function, as a result from such supplementation, since its toxicological effects are still controversial in scientific literature 30 . Studies have shown that creatine supplementation did not cause damage to kidney and liver function in rats 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Creatine supplementation has become popular from the Olympic Games of Barcelona in 1992 and is currently one of the most popular protein supplements used by athletes and physical activity practitioners (1,2) . There is evidence that the creatine amount stored may be the limiting factor of physical performance in high intensity and short duration exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Shao and Hathcock (4) , after extensive work, verified that after two and a half decades of experimental and clinical studies with different dosage and times of supplementation, in only two cases of volunteers supplemented with creatine renal complication have been reported, but which came from periods previous to these experiments. However, despite the strong evidence of this substance as an ergogenic agent, it is still not unkown about possible hepatic and renal alterations derived from creatine supplementation, demanding hence further studies on this supplementation safety (2,5,6) . A hypothesis that creatine supplementation modifies the renal and hepatic functions in individuals clinically normal is brought about from the shortage of evidence on the potential adverse effects derived from the supplementation with monohydrate creatine in the hepatic and renal function.…”
Section: Introductionmentioning
confidence: 99%